Sustentabilidade da vida: cartografia de saberes socioambientais dos(as) alunos(as) do ensino médio da Escola Família Agroextrativista do Carvão, na Amazônia Oriental-AP - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
The objective of the thesis was to understand the ecology of knowledge of the 2nd and 3rd grades of high school at the Carvão Agroextractivist Family School and its integration into the students' educational process. In this sense, the research entitled "Sustainability of Life: Cartography of Socio-environmental Knowledge of High School Students of the Carvão Agroextractivist Family School, in the Eastern Amazon - AP" was developed in the aforementioned school, located in the District of Carvão – Queimadas Branch Line, Mazagão – AP. It was developed through a qualitative and quantitative approach, of the type case study, having as moments: 1) bibliographic survey; 2) documentary survey; 3) application of questionnaire; 4) socio-environmental cartography – using generative themes; 5) analysis and interpretation of data – based on Fleck's conceptions (collective thought) and on the Theory of Social Representations. The study was justified by the understanding that the sustainability of life will be constituted from the practice of a formidable, emancipatory and comprehensive educational process - which considers the diversity of knowledge present in the daily routine of the life territories of traditional communities, for the formation of ecological conscience that will guarantee natural capital for present and future generations. The results found were based on the recognition of the Ecology of Knowledge and their integration in the educational praxis developed by EFAC from the appreciation and recognition of its territorialities, since, through the pedagogy of alternation - based on the principles: Local Association, Comprehensive Training, Alternation and Development of the Environment - the school develops its Pedagogical Political Project
Keywords: Ecologia de saberes; Educação rural - Distrito do Carvão (Mazagão, AP); Território; Sustentabilidade; CNPQ::CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL; EDUCAÇÃO, CULTURAS E DIVERSIDADES; EDUCAÇÃO, POLÍTICAS E CULTURAS